EFEKTIVITAS BUKU AJAR BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) PADA MATERI ELASTISITAS DAN HUKUM HOOKE SISWA KELAS XI SMA NEGERI TUGUMULYO TAHUN PELAJARAN 2018/2019. - S, Novitasari (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2019)
This study aims to determine the learning outcomes of class XI students in Tugumulyo State Senior High School 2018/2019 Academic Year after using the physics-based teaching material of elasticity and hooke’s law and to find out the students response to learning using the higher order thinking skills approach to elasticity and hooke’s law material of class XI students at Public High School Tugumulyo 2018/2019 Academic Year. The population of this study were all students of class XI and the subject of this study consisted of 34 students of class XI IPA 5 of State Senior High School Tugumulyo. Data collection is done by questionnaires, tests, and observations. The overall percentage of teaching material components was 79,24% (very good). The percentage of student responses to higher order thinking skills -based teaching materials is 76,53% (very good). In addition, from the results of daily test tests, the effectiveness percentage of 88.89% (very good) of students who scored above 70 out of 10 test items. The value of t count> t table with the value of t count = 2,13and t table = 1,697. So that the use of higher order thinking skills -based teaching materials can be said to be valid, practical and effective.